Antimicrobial role of Lactobacillus species as potential probiotics against enteropathogenic bacteria in chickens - Zulfiqar Ahmed; Muhammad Sufyan Vohra; Muhammad Noman Khan; Ayaz Ahmed; Taseer Ahmed Khan (Journal of Infection in Developing Countries)
Introduction: The emergence of antimicrobial resistance among bacterial community resulted in a ban on drugs as the growth promoter in poultry feed. This situation demands to explore alternatives as food supplements with health benefit to poultry. Therefore, probiotic microorganisms, which are considered as safe and possess various health benefits can be a choice. Present study was designed to explore the probiotic potential of the isolated lactobacillus species in chickens.